Genetic interactions between Drosophila melanogaster menin and Jun/Fos - Cerrato, Aniello (2006)
Menin is a tumor suppressor required to prevent multiple endocrine neoplasia in humans. Mammalian menin protein is associated with chromatin modifying complexes and has been shown to bind a number of nuclear proteins, including the transcription factor JunD. Menin shows bidirectional effects acting positively on c-Jun and negatively on JunD. We have produced protein null alleles of Drosophila menin (mnn1) and have over expressed the Mnn1 protein. Flies homozygous for protein-null mnn1 alleles are viable and fertile. Localized over-expression of Mnn1 causes defects in thoracic closure, a phenotype that sometimes results from insufficient Jun activity. We observed complex genetic interactions between mnn1 and jun in different developmental settings. Our data support the idea that one function of menin is to modulate Jun activity in a manner dependent on the cellular context.